UNDERSTANDING TAXPAYERSâ ADOPTION OF ONLINE TAX RETURN REPORTING WITH AN EXTENDED META- UTAUT MODEL - Heri Hermanto, Asep
This research examines dominant technology adoption paradigms to discover vital underlying variables in online tax return reporting behavior. This research aims to develop and empirically test a hypothetical model based on data collected from Indonesia's existing online tax return reporting users. This research was conducted by distributing an online questionnaire nationwide and obtaining 486 taxpayer data for further analysis. The findings show that trust, effort expectancy, and performance expectancy positively and significantly impact taxpayers' attitudes towards online tax return reporting. Facilitating conditions and attitudes positively and significantly impact the taxpayer intention to adopt online tax return reporting. However, the intention of taxpayers to use online tax return reporting is unaffected by social influence. Taxpayers' behavioral intentions positively and signi?cantly impact their user behavior. At the same time, grievance redressal and anxiety had a significant influence as moderating variables. Based on the thematic analysis results of the answers to open-ended questions at the end of the questionnaire, positive experiences, negative experiences, and suggestions for improvement were obtained. Positive experiences from respondents who have used the online tax return reporting application are fast and efficient, easy to use, flexible, helpful and Ecofriendly. The negative experience is that applications often error and are difficult to